Interpretation of the DermaLab Combo® pigmentation and vascularity measurements in burn scar assessment: An exploratory analysis. Issue 6 (September 2015) - Gankande, T.U.; Duke, J.M.; Wood, F.M.; Wallace, H.J.
Highlights The DermaLab Combo® is an objective and reliable tool for burn scar assessment. Continuous numerical data are generated – suitable for identifying changes over time. The DermaLab Combo® measurements can be interpreted using % change in scar compared to normal skin. Cut-offs values using two variables (melanin and erythema) for categorisation of pigmentation were determined. Further validation of the DermaLab Combo® in scar assessment is needed.